PENINGKATAN HASIL BELAJAR SEJARAH MELALUI STRATEGI COOPERATIVE LEARNING TEKNIK JIGSAW SISWA KELAS XI IPS 1 SMA NEGERI 1 MAUMERE SEMESTER 1 TAHUN PELAJARAN 2017/2018 - TEODORA TIMU (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
Classroom action research (PTK) with the title Efforts to Increase Learning Achievement History Through Cooperative Learning Strategy Jigsaw Student Class XI IPS 1 SMA Negeri 1 Maumere Semester 1 Year Lesson 2017/2018 aims to increase interest, liveliness and learning achievement of learners of subjects history especially the material development of society and culture in Indonesia which is patterned Islam. This research was conducted in class XI IPS 1 SMA Negeri 1 Maumere . The study was conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection. Sources of research data include: informants, places and events, and documents. Data were collected using direct observation techniques, tests and document records. The result of this research concludes that the application of cooperative learning strategy of jigsaw technique can increase interest, activity and learning achievement of students of history subject from average value 75,44 with learning completeness 79,41% in cycle I to 79,56 with mastery learning 97.06 on cycle II.